Antiviral therapy for chronic hepatitis C in 2014. Issue 4 (July 2014) - Nookathota, Manogna; Mukherjee, Sandeep
<x xml:space="preserve">Abstract</x> An all-oral therapy for treating hepatitis C (HCV) is now available for the most common genotypes although interferon-based therapy is still recommended for interferon-eligible patients with HCV genotype 1. For most patients, a prior history of treatment or presence of cirrhosis does not appear to significantly impact eradication rates with direct acting antivirals (DAA). The promising results from the numerous clinical trials of DAA's for HCV together with their tolerability represent a tremendous advance in our management of this disease, particularly as treatment is often well-tolerated, associated with few side effects and significantly shortened in duration. We will review several of the peer-reviewed landmark studies of DAA's for the treatment HCV and conclude with an expert commentary and five year view.